Study on the macro-micro properties of fly ash ceramic granulated concrete (FACGC) under the coupling of curing regime and freeze-thaw media - Jin Qu; Haitao Mao; Xiaoju Wang; Chang Liu (Case Studies in Construction Materials)
The utilization of fly ash ceramic granulated concrete (FACGC) has been observed in the construction of lightweight prefabricated structures, such as long-span bridges and high-rise buildings. The performance of FACGC is greatly influenced by the coupling effects of steam curing and salt-freezing. This study investigates the alterations in the macroscopic characteristics of FACGC test blocks under freeze-thaw cycles in water and aqueous NaCl solution (3 %), considering both standard curing and steam curing conditions. Scanning electron microscopy (SEM) and nuclear magnetic resonance (NMR) were employed to uncover the internal deteriorating mechanism at the microscopic level. The findings indicate that the coupling of salt freezing and steam curing leads to the most significant degradation of mechanical properties and internal pore structure. During the initial 50 freeze-thaw cycles, the mass loss rate initially increases and subsequently decreases across different media. As the number of cycles increases, the mass loss rate and compressive strength loss rise sharply, while the relative dynamic elasticity modulus declines abruptly. The salt-frozen group exhibits abrupt changes 1–2 cycles earlier than the water-frozen group. Nevertheless, the incorporation of fly ash, slag, and silica fume results in a notable enhancement of their strength, ranging from 10 % to 20 %. Additionally, this combination leads to a delay of 1–2 freeze-thaw cycles in reaching the failure threshold. The coupling of steam curing and freeze-thaw resulted in a more rapid formation of large pores and micro-cracks, and the porosity of the test block exhibited a significant increase of 163.78 % when compared to the test block subjected to water freezing and conventional curing. The degradation of the pore size of coal ash ceramic concrete was shown to be influenced by the salt solution in the following sequence: medium pores > large pores > micro-cracks > small pores. Furthermore, the coupling of salt freezing and steam curing increases the calcium-to-silicon (Ca/Si) ratio and reduces internal polymerization degree, while the incorporation of fly ash, slag, and silica fume into the cementing material enhances the internal pore structure and effectively fills the small pores, thereby improving the microscopic properties of FACGC.